Effects of Deqi on Autonomic Balance in Adult Tinnitus Patients: Study Design of a Randomized Controlled Trial. (29th July 2013) - Li, Qian-Qian; Shi, Guang-Xia; Fu, Xin-Xing; Han, Li-Li; Liu, Li-Ying; Liu, Cun-Zhi; Wang, Lin-Peng; Hou, Na
Abstract : Background . Recent reports suggest that a proportion of tinnitus patients suffer from mental illness. Autonomic nervous system plays a useful role in tinnitus therapy since electrical vagal nerve stimulation (VNS) has been frequently used to alleviate tinnitus-induced depression in clinic. heart rate variability (HRV), which is reflective of autonomic nervous system function, has been proved to be modulated by acupuncture. In the present study, we aim to compare the effect of deqi sensation on heart rate variability in adult tinnitus patients. Methods . Thirty participants are randomly assigned to verum acupuncture (creating deqi) or shallow acupuncture (not creating deqi) at Baihui (Du-20), Shenting (Du-24), Tinghui (GB-2), Waiguan (SJ-5), and Zulinqi (GB-41) for 3 weeks. The primary outcome measure is heart rate variability, which is measured at the first acupuncture, as well as the last acupuncture. Discussion . Completion of this trial will help to identify the role of deqi sensation in acupuncture effect for tinnitus and reveal an autonomic modulation mechanism for acupuncture effect. Trial Registration . This trial is registered with International Standard Randomised Controlled Trial Number ISRCTN58013563 .